Combustion of H2/air supersonic mixing layers with splitter plate: Flame structure and statistical characteristics - Xiao, Yao; Jianguo, Tan; Dongdong, Zhang; Yao, Liu (Acta astronautica, 2020)
H2/air supersonic mixing layers were calculated with different splitter plates thickness. The accumulation of OH radicals between the most reactive and stoichiometric mixture fraction causes the corresponding change of reactions. With the increase of plate thickness, flame surfaces tend to be more wrinkling. Especially in the initial developing stage, the distribution of temperature, scalar dissipation, Damkohler number and Takeno index is closely related to plate thickness. However in the developed stage, the distribution shows similarity. The symmetry of scalar dissipation rate built in the initial developing zone is broken in the developed stage, corresponding to the distribution about production terms of scalar variance [1]. Different from circulation and developed zone, premixed combustion take a more important part in the initial developing stage. Same as the change of flame curvature, autoignition effect dominating heat release increases first and decreases lately along streamwise direction. •●The accumulation of OH radicals causes the corresponding change of reactions.•●With the increase of plate thickness, flame surfaces tend to be more wrinkling.•●In the initial developing stage, T, χ, Da and Gfo is closely related to plate thickness.•●In the developed stage, the distribution shows similarity.•●Premixed combustion take a more important part in the initial developing stage.